Chimeric Antigen Receptor T-Cell Therapy Clinical Results in Pediatric and Young Adult B-ALL - Amanda M. DiNofia; Shannon L. Maude (HemaSphere, 2019)
Abstract. Chimeric antigen receptor (CAR)-modified T-cell therapy has revolutionized the care of patients with relapsed and refractory B-cell acute lymphoblastic leukemia (B-ALL). Results from clinical trials across multiple institutions report remarkable remission rates with CD19-directed CAR-modified T-cell therapy. These remissions are also proving to be durable in many patients with a relapse-free survival (RFS) of approximately 50% to 60% at 1 year across several trials and institutions in this population that has been historically very difficult to treat. In addition, new products are being developed to enhance upon the original CAR T-cell products, which include a humanized CAR, allogeneic CARs, and both CD22 and biallelic CD19 and CD22 constructs. Toxicity after CAR-modified T-cell therapy is characterized by cytokine release syndrome (CRS) and neurotoxicity in the acute post-infusion period and B-cell aplasia as a long-term consequence of treatment. This review will summarize the published data thus far on the use of CAR-modified T-cell therapy in pediatric B-ALL and outline the various CAR products now being developed for this population. Delivery of this therapy and the decision to pursue hematopoietic stem cell transplant (HSCT) after treatment will be discussed.